A formação integral da pessoa em Edith Stein : perspectivas teológicas e pedagógicas - Teixeira, Patrícia Espíndola de Lima (2017)
A present research proposes to carry a dialogue between Education and Theology and to comprehend anthropology as a pedagogical guideline to form of the human person. In order to achieve this, it analyzes the bibliographic records of the German philosopher, Edith Stein (1891-1942), especially in her work "The Structure of the Human Person" - Der Aufbau der menschlichen Person. As Stein’s contributions to the educational field, they start from studies in phenomenology articulated with development on philosophical-theological anthropology. Edith Stein's work emphasizes the completeness of the person as bodypsyche- spirit. Emphasizing the importance of the philosopher's multidisciplinary personality, the text is part of a hybrid from the author’s both life and work, follows in its concept of formation and encounters with the sense of educating "from within", and completes with the analysis of the human person from the perspective of Christian revelation. Conclusively, Edith Stein points to the anthropological basis as the primacy to all formative activity, identifying totality, uniqueness and unrepeatability with which each person is constituted and invoked to a life of reciprocity with the other, through the empathic relationship. As a major formative sphere, Stein’s pedagogy emphasizes divine grace as the force that comes to meet human nature.